GE_GERICHTE C/16103/2011 vom 18. Juli 2012 - GE Cour de justice (2012)
HEURES DE TRAVAIL SUPPLÉMENTAIRES ; TORT MORAL ; INDEMNITÉ DE VACANCES ; SALAIRE | CPC.317.1 / CO.335 / CPC.244.1 / CPC.246 / CO.321.c.3 / CC.8